An Analysis on the Speech Act of Prilly Latuconsina "Break the Glass Ceiling" in English Speech Youtobe Channel - Mar'atus sholikah (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2023)
This study aims to analyze types of speech acts and classification of illocutionary speech acts occuring in Habibie and Ainun's conversation in film entitled Habibie and Ainun 2012. This is a qualitative descriptive study conducted on naturalistic investigations of social phenomena. Data were analyzed based on theory of speech acts types put forward by Yule (1996). Analysis of classification of illocutionary speech acts put forward by Searle (1977) which consists of, representative, directive commissive, expressive and declaration. Results of this study indicate that there are five classifications of illocutionary speech acts. It was found that there were a total of 42 utterances analyzed as illocutionary where 5 utterances were representative, 9 declarative utterances, 23 directive utterances, 5 expressive utterances, and no commissive (0%) . This study shows that speech "Break the Glass Ceiling" by Prilly Latuconsina contains various types of speech acts that aim to influence, inspire, and motivate listeners. This speech had a strong impact in raising awareness on gender equality issues and encouraging positive action to achieve success. Implication of this research is studying and mastering pragmatics, especially in speech act theory to be able to understand intent of the speaker so that communication expressed can be fulfilled.